PENERAPAN PENDEKTAN PROBLEM CE PENERAPAN PENDEKTAN PROBLEM CENTERED LERANING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR LATERAL MATEMATIS SISWA DI SMP - Ayen Arsi Sari (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2018)
THE APPLICATION OF PROBLEM CENTERED LEARNING APPROACH TO ENHANCE THE ABILITY TO THINK LATERAL MATHEMATICAL OF STUDENTS OF JUNIOR HIGH SCHOOL Ayen Arsisari, M.Pd Program Studi Pendidikan Matematika STKIP Muhammadiyah Bangka Belitung Jl. KH. Ahmad Dahlan KM 4 Pangkalanbaru, Ayenarsisari@yahoo.co.id ABSTRACT This research is based on the issues of lowness of lateral thinking ability of junior high school students in mathematical lesson. The purpose of this research is to observe the upgrading of mathematical lateral thinking ability mathematical among students who received PCL (Problem Centered Learning) approach and conventional learning. This research is a research quasi experimental design with a non-control group equivalen using Purposive Sampling Technique which the subject is students in one of junior high school in Bandung, while the samples are students of experimental class which is amounted to 34 students and students of control class which is amounted to 34 students. The instruments that used are the initial mathematics ability test, test of the ability to think laterally mathematical and the sheets of teacher and students observation. Quantitative analysis is carried out using the average difference test and anova test two lines. The results show that (1) The upgrading of mathematical lateral thingking of students who received PCL approch is better than students who just received conventional learning; (2) There is the upgrading difference of mathematical lateral thinking of students who received PCL approachi viewed from the initial mathematics ability (high, middle, low) (3) There is interaction between the learning approach that used (PCL, conventional) with KAM (high, middle, low) and the upgrading mathematical lateral thinking of students;